2019
DOI: 10.1590/1413-81232018246.19612017
|View full text |Cite
|
Sign up to set email alerts
|

Revisión sistemática de instrumentos de violencia en el noviazgo en Iberoamérica y evaluación de sus propiedades de medida

Abstract: Resumen Ser una víctima o perpetrador de violencia en el noviazgo se ha asociado con mala salud mental, consumo de sustancias y riesgos sexuales. El objetivo fue realizar una revisión sistemática y evaluar la calidad de las propiedades de medida de instrumentos de violencia en el noviazgo, creados o adaptados en Iberoamérica de 1981 a 2017, para población de 12 a 29 años y publicados en español, inglés, portugués o francés. La búsqueda se realizó en PubMed, ISI Web of Knowledge, EBSCO, ScienceDirect, SCOPUS, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(82 reference statements)
0
5
0
2
Order By: Relevance
“…The quality and risk-of-bias assessment used the AXIS and Downs and Black Checklist 31 tools, as there are no instruments that can help to assess these properties in the field of psychology 70 and the AXIS tool was used to evaluate successful studies in the field of psychology 33 ; most of the scales and verification lists are used in epidemiological studies or aim at evaluating clinical trials 32,71 .…”
Section: Discussionmentioning
confidence: 99%
“…The quality and risk-of-bias assessment used the AXIS and Downs and Black Checklist 31 tools, as there are no instruments that can help to assess these properties in the field of psychology 70 and the AXIS tool was used to evaluate successful studies in the field of psychology 33 ; most of the scales and verification lists are used in epidemiological studies or aim at evaluating clinical trials 32,71 .…”
Section: Discussionmentioning
confidence: 99%
“…Respecto a el instrumento de medición, cabe destacar que el más utilizado fue el cadri, el cual ha presentado evidencia favorable de propiedades psicométricas (Exner-Cortens et al, 2016;Yanez-Peñúñuri et al, 2019). De los 27 estudios, solo dos midieron tanto la violencia cara a cara como la digital (Thulin et al, 2021;Zweig et al, 2014).…”
Section: Discussionunclassified
“…This is not surprising if one considers an international research context where it seems that there are still few instruments that specifically and comprehensively evaluate violence against young people, considering the physical, sexual, control, and psycho-emotional dimensions, both in the violence exerted and received (García-Carpintero, Rodríguez-Santero & Porcel-Gálvez, 2018). Therefore, it is necessary to continue updating the knowledge about the properties of the instruments used in the region to measure DV (Yanez-Peñúñuri et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it should be noticed that there are numerous systematic reviews on DV in the international context that focus on different aspects, such as factors associated with DV (Gracia-Leiva et al, 2019), prevalence (Rubio- Garay et al, 2017), the instruments (López-Cepero, Rodríguez-Franco & Rodríguez-Díaz, 2015;Yanez-Peñúñuri, Hidalgo-Rasmussen & Chávez-Flores, 2019a), the interventions (Alegría & Rodríguez, 2015;Yanez-Peñúñuri, Martínez-Gómez & Rey-Anacona, 2019b), or the emergence of other types of violence (Rodríguez-Domínguez, Pérez-Moreno & Durán, 2020). Currently, however, up to the time of carrying out this study, narrative reviews can only be found within the Mexican context on DV among adolescents (Rojas-Solís, 2013a) and Mexican university students (Rojas-Solís, 2013b).…”
Section: Dating Violence In University Studentsmentioning
confidence: 99%